NGO-Corporate Partnerships: Sustainable Development Impact for Indian Children - Karina Erdian Hapsari (Insignia: Journal of International Relations, 2022)
This paper reviews the importance of NGO-corporate partnerships towards sustainable development for Indian children. Specifically, this paper analyzes CRY India and the three big corporations – Marks & Spencer, Microsoft, Bajaj Finserv – as the research subject. The NGO-corporate partnerships are crucial in the sustainable development process. Moreover, in India, the number of child labor is increasing. Thus, in order to achieve sustainable development, the child labor issue must be tackled in the right ways as children are the basis for all dimensions of sustainable development. For analysis, this paper uses an explanative approach, with secondary data. The analysis found that there are two reasons to explain their significant partnerships, as a ‘bridge’ between the actors and long-term potential value. A bridge between the actors in this paper refers to CRY India-three big corporations (Marks & Spencer, Microsoft, Bajaj Finserv) interrelations. These interrelations illustrate the needs of NGOs in funding and on the other hand, NGOs provide ‘space’ for corporate social responsibility through their programs. A ‘space’ in this paper refers to the access given by CRY India for corporates to do their CSR through CRY India’s projects as an altruistic action for both CRY and corporates. Meanwhile, the potential value leads to the benefit and impact that goes beyond partnerships, which is a better sustainable development for Indian children. In conclusion, the NGO-corporate partnerships are still needed to tackle today’s problem, and it might give an incredible impact. Though, there are some debates about their relations.